Pengaruh Gaya Hidup dan Citra Merek terhadap Keputusan Pembelian Sepeda Motor Sport Kawasaki Merek Ninja di Surabaya - Sergian Baihaki; Supriyono Supriyono (Universitas Batanghari, 2023)
This study aims to determine the effect between lifestyle and brand imaged on purchasing decisions on Kawasaki Ninja Sport Motorcycle in Surabaya. The study used quantitative method through a population approach of Kawasaki Ninja’s owners in the city of Surabaya. Data was collected by non-probability sampling, also purposive sampling techniques with total of 66 respondents. The data collection method is raised through survey results engaged with Partial Least Square software as analysis tool. The research shows that the lifestyle and the brand image have a significant influence on purchased decision of Kawasaki Ninja Sports Motorcycle. Then it can be concluded as the higher between lifestyle demand, also the better brand image for the brand, it will affect on buying decision for the Kawasaki Sports Motorcycle in Surabaya.